PEMILIHAN ENGINEERING CONTRACTOR PROYEK DANA HIBAH ENERGI TERBARUKAN DENGAN METODE DEMATEL DAN ANP - Pambudi, Agus Setyo (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
One of the success keys of the grant fund program for the renewable energy project is in the decision making process to find the engineering contractor with the best quality, effectiveness, and efficiency to implement the process of procurement of goods and services. The objective of this research is to design a systematic selection model for the engineering contractor referring to the conditions, situations, and scopes as required by the